Conversion surgery for stage IV gastric cancer after third-line immunotherapy: a case report - Evdokimova, Sevindzh F.; Kornietskaya, Anna L.; Bolotina, Larisa V.; Kolobayev, Iliya V.; Fedenko, Alexander A.; Kaprin, Andrey D. (Frontiers in Oncology, 2024)
The 5-year overall survival rate for stage IV gastric cancer is lower than 10%, despite the development of systemic therapy. Conversion surgery has shown to improve survival outcomes in patients with durable clinical response on chemotherapy. We report a clinical case of a patient, who underwent conversion surgery after pembrolizumab in the third-line setting for stage IV gastric cancer. The patient did not have recurrence for 22 months after conversion surgery.